Clinicopathological correlation of adenoid cystic carcinoma: A notorious masquerader and clinical paradox - Preeti Sharma; Vidya Jha; Ashish Kumar Mandal (Indian Journal of Medical and Paediatric Oncology)
Background: Adenoid cystic carcinoma (ACC) is an uncommon tumor with nonspecific clinicoradiological features thereby masquerading other nonneoplastic and neoplastic entities. Materials and Methods: Cases of ACC were retrospectively reviewed over a period of 4 years. The clinical details of these patients including fine-needle aspiration cytology (FNAC) and imaging findings were retrieved. Diagnosis was confirmed on histomorphology and supplemented with immunohistochemistry (IHC). Results: Thirty cases of ACC were included in the study. Mean patient age was 55.5 years with a slight female preponderance. Among the 30 ACCs, 10 (33.4%) were located in submandibular gland, 7 (23.4%) in parotid gland, 6 (20%) in sublingual gland, 2 (6.7%) in lung and one each (3.33%) in nasal cavity, breast, cervix, lip, and skin of face. Preoperative imaging was suggestive of malignancy in 29 cases while a single case of parotid gland ACC was misdiagnosed as benign salivary gland neoplasm. FNAC was performed in 29 cases with a diagnostic accuracy of 82.7%. Histopathological examination showed characteristic features of ACC in all cases with perineural invasion seen in 7 cases. On IHC, positivity for cytokeratin was seen in all cases, cluster of differentiation 117 in 24 cases, thyroid transcription factor-1 in two cases and human epidermal growth factor receptor/neu in two cases. All cases were negative for estrogen receptor and progesterone receptor IHC. Mean Ki-67 score was 47.8%. Conclusion: ACCs are notorious tumors showing slow growth kinetics with propensity for perineural invasion, late recurrences, and distant metastasis. It should be kept in mind as a differential diagnosis at unusual sites other than salivary glands.